Genetic variability, heritability and correlations for milling and grain appearance qualities in some accessions of rice (Oryza sativa L.) (2020)
Poor milling and grain appearance is a common feature of locally produced rice (Oryza sativa L.) in West Africa. Development of genotypes with high yield and uniform milled grain size will enhance the market for the locally produced rice. One hundred rice accessions were evaluated to assess genetic variability, heritability and correlations for 11 milling and appearance quality traits and grain yield. The field was laid as a 10 9 10 alpha lattice design with three replications following standard cultivation practices. ANOVA revealed significant differences for the traits studied. The genotypic and environmental variances showed significant differences for all characters studied. Phenotypic coefficient of variation was greater than its corresponding genotypic coefficient of variation for each studied trait. Heritability at broad-sense varied from 14.1% for milling degree to 73.8% for milled grain length-to-width ratio (L/W). Genetic advance as percent of mean ranged from 2.2% for brown rice recovery to 129.6% for percentage of grain with chalkiness (PGWC). In general, genotypic correlations ranged higher than their corresponding phenotypic correlations. Brown rice recovery had significant positive phenotypic and genotypic correlations with milling recovery and head rice recovery. Consequently, brown rice recovery, milling recovery and L/W could be used as selection criteria for the improvement of head rice recovery. Genotypes BETIA and CRI-AMANKWATIA had the desirable PGWC and degree of chalkiness, therefore, they are recommended for the improvement of high yielding varieties with high amount of chalkiness.